Patella baja after the modified Coventry-Maquet high tibial osteotomy - Backstein, David; Meisami, Borna; Gross, Allan E (The Journal of knee surgery, 2003)
This study assessed the Modified Coventry-Maquet technique for high tibial osteotomy with respect to the incidence of patella baja using the Insall-Salvati index. Twenty-seven high tibial osteotomies performed or supervised by a single surgeon (A.E.G.) between 1996 and 2000 were analyzed. Eight knees were excluded; the remaining 19 were evaluated. Mean patient age at surgery was 49 years, and the mean postoperative Insall-Salvati index was 0.83. This represented an average decrease in patellar height of 15% (P<.000001). The incidence of new-onset postoperative patella baja was 26% (5/19). Tibial posterior slope increased by an average of 4.3 degrees (P<.0001). Mean tibial tuberosity height decreased by an average of 8.9 mm (P<.0001). The mechanical axis was corrected by an average of 11.9 degrees and loss of range of motion postoperatively was negligible. The correlation between tibial slope, tuberosity height, and patellar height was not significant. The modified Coventry-Maquet procedure achieved excellent valgus knee realignment while losing minimal range of motion and avoiding intra-articular fracture and nonunion. This incidence of patella baja was comparable to most, and better than some, published series.